ANALYSIS OF ENERGY EFFICIENCY PERFORMANCE USING THE MEMBERSHIP FUNCTION (MF) METHOD IN A FUZZY LOGIC CONTROL SYSTEM FOR RESIDENTIAL SPLIT AIR CONDITIONERS (AC) - Susilo, Susilo; Lalay, Ario Azadi (PT. Jurnal Center Indonesia Publisher, 2025)
A fuzzy logic-based control system in household split-type air conditioners (AC) offers an alternative approach to reducing excess energy consumption without compromising thermal comfort. This study aims to test the effectiveness of three types of membership functions (MF), namely triangular, trapezoidal, and Gaussian, in improving energy efficiency and the stability of room temperature and humidity control. Simulations were performed using MATLAB software with the Mamdani fuzzy inference method and centroid defuzzification technique. The three MF were tested using 30 sets of temperature and humidity data to analyze their effect on fan speed and power consumption. The simulation results show that the trapezoidal MF provides the highest energy efficiency of 57.24%, followed by the Gaussian MF at 56.80% and the triangular MF at 53.71%. These findings indicate that fuzzy systems can significantly reduce energy consumption compared to conventional air conditioner controllers. This research is expected to serve as a reference in the development of more energy-efficient intelligent control systems.